Evaluation of the Sf-12. Usefulness of the Mental Health Scale [Evaluación del Cuestionario Sf-12: Verificación de la Utilidad de la Escala Salud Mental] - Vera-Villarroel, P; Pavez-Salinas, P; Celis-Atenas, K (Sociedad Medica de Santiago, 2014)
Background: The SF-12 is one of the most used questionnaires to evaluate the multidimensional health related quality of life, worldwide. However, the factor structure does not match the structure of the original instrument. Besides, most studies centered in the physical dimension paying less attention to mental health related quality of life. Aim: To evaluate the psychometric properties of the SF-12 and to validate the mental health dimension of this questionnaire. Material and Methods: Two studies were conducted, the first consisting of 840 people aged between 18 and 60 years, who answered the SF-12. In the second study, 970 people aged between 18 and 60 years answered the SF-12 questionnaire, the Beck Depression Inventory (BDI) and the State-Trait Anxiety Inventory (STAI). Reliability (internal consistency and temporal stability) was analyzed, along with construct and criterion validity for the mental health dimension. Results: The reliability estimate using Cronbach’s alpha in both studies was higher than 0.74 in both dimensions (physical and psychological). Construct validity analysis yielded a three factor complex solution. Finally the criterion validity analysis showed appropriate and significant correlations with depression and anxiety. Conclusions: The SF-12 and its mental health scale are suitable for epidemiological characterization studies. © 2014, Sociedad Medica de Santiago. All rights reserved.